A Systematic Literature Review of Motivation, Trust, and Purchase Intention in Live Shopping Commerce: Toward an Integrated S-O-R Conceptual Model - Anisah Mutmainah; Reny Nadlifatin (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
The rapid growth of live shopping highlights the complex psychological mechanisms driving purchase intentions. However, previous research remains highly fragmented, often examining motivational or trust aspects in isolation. This study addresses this gap by developing an integrated conceptual model linking motivation and trust to consumer purchase intentions. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines. From an initial retrieval of 210 records, studies were systematically screened for relevance and appraised for quality, resulting in 40 empirical articles (2017–2025) extracted from the Google Scholar database using Publish or Perish. While relying exclusively on Google Scholar is a methodological limitation, it provides a practical baseline for this review. The synthesized literature underscores the Stimulus-Organism-Response (S-O-R) framework's dominance. Findings indicate that social and hedonic motivations act as dominant stimuli triggering social presence. Crucially, this engagement builds multidimensional trust in the streamer, which is subsequently transferred to the platform and product, reducing uncertainty and driving purchases. The proposed model integrates these effective and cognitive pathways into an evidence-based framework. Ultimately, the study demonstrates that social interaction precedes cognitive trust formation, providing a structural baseline for future empirical validation in live commerce.